PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER SISWA SMK SWASTA YPII TANJUNG PURA - Ika Mustika Dewi; Syahrul Kodrah (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2024)
The respondents in this study were Islamic Religious Education teachers, school principals and students at YPII Tanjung Pura Private Vocational School. Data collection techniques by means of observation, interviews and documentation. Data analysis techniques are data reduction, data presentation and drawing conclusions. The results of the research explain the role of Islamic Religious Education teachers in shaping the character of YPII Tanjung Pura Private Vocational School students, namely character development through habituation, character formation through attention, character formation through providing motivation, character formation through punishment. The forms of character building activities carried out by Islamic Religious Education teachers in shaping the character of students at YPII Tanjung Pura Private Vocational School, namely teaching based on the curriculum that has been implemented in the RPP, holding express Islamic boarding school activities, through competition activities in commemoration of Islamic holidays, and social activities. The obstacles faced by Islamic Religious Education teachers in shaping the character of students at the YPII Tanjung Pura Private Vocational School are family factors, environmental factors in students' playing and social interactions, lack of cooperation between religious teachers and their parents, students' characters that are difficult to form, and advances in technology. Meanwhile, the solution is to provide supervision, appeal and advice, provide punishment, collaborate with teachers and parents, and provide awards in the form of praise.